2021
DOI: 10.3390/ijms22041534
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Redox Metabolism in Pancreatic Cancer

Abstract: Cell metabolism is reprogrammed in cancer cells to meet their high bioenergetics and biosynthetic demands. This metabolic reprogramming is accompanied by alterations in redox metabolism, characterized by accumulation of reactive oxygen species (ROS). Elevated production of ROS, mostly by mitochondrial respiration, is counteracted by higher production of antioxidant defenses (mainly glutathione and antioxidant enzymes). Cancer cells are adapted to a high concentration of ROS, which contributes to tumorigenesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 109 publications
1
11
0
Order By: Relevance
“…Herein, cells were treated with RuRe-1 and RuRe-2 for 6 h and then stained with 2′,7′-dichlorodihydrouorescein diacetate (H 2 DCFDA). H 2 DCFDA is non-fluorescent and can be oxidized by intracellular ROS to highly fluorescent 2′,7′-dichlorofluorescein (DCF) ( Abdel Hadi et al, 2021 ). The intensity of green fluorescence can respond to the accumulation of intracellular ROS.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, cells were treated with RuRe-1 and RuRe-2 for 6 h and then stained with 2′,7′-dichlorodihydrouorescein diacetate (H 2 DCFDA). H 2 DCFDA is non-fluorescent and can be oxidized by intracellular ROS to highly fluorescent 2′,7′-dichlorofluorescein (DCF) ( Abdel Hadi et al, 2021 ). The intensity of green fluorescence can respond to the accumulation of intracellular ROS.…”
Section: Resultsmentioning
confidence: 99%
“…Current “ROS threshold” theories suggest that along with increases in ROS, cell responses change from proliferation to balance and then to cell death after ROS surpass a certain level [ 45 ]. Mild-to-moderate levels of ROS are associated with the activation of protomourigenic survival and growth pathways, while excessive concentrations of ROS can lead to the induction of cell cycle arrest and cell death [ 20 , 25 , 26 ]. In accordance with this, it has been reported that higher expression of MAP17 and SGLT-1 was correlated with better prognosis in laryngeal and cervical cancers [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it could stimulate the specific Na-dependent transportation of mannose and glucose in Xenopus oocytes and human tumour cells and was overexpressed in a variety of human carcinomas, enhancing the tumorigenic phenotype by increasing intracellular ROS [ 12 , 14 19 ]. ROS are oxygen-derived molecules, mostly the free radicals superoxide anion O 2 − and hydroxyl radical -OH, and they can promote cancer development, chemoresistance, and relapse by causing oxidative DNA damage and genomic instability and modifying gene expression [ 20 23 ]. It has been reported that the levels of ROS are notably increased in patients with pancreatic cancer and are involved in the progression, drug resistance, recurrence and metastasis of pancreatic cancer [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Hfe −/− mice on ND showed increased mitochondrial superoxide production, even without additional dietary iron loading. This might have been caused by the elevation in mitochondrial respiratory capacity as Complexes I and III are able to produce increased radical amounts [59].…”
Section: Dietary and Genetic Iron Overload Increased Liver Mitochondrial Superoxide Formationmentioning
confidence: 99%